2020
DOI: 10.1162/qss_a_00038
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in citation impact for 27 fields and six English-speaking countries 1996–2014

Abstract: Initiatives addressing the lack of women in many academic fields, and the general lack of senior women, need to be informed about the causes of any gender differences that may affect career progression, including citation impact. Previous research about gender differences in journal article citation impact has found the direction of any difference to vary by country and field, but has usually avoided discussions of the magnitude and wider significance of any differences and has not been systematic in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 48 publications
(52 reference statements)
3
26
0
4
Order By: Relevance
“…Full results and details of regression fitting are in the supplementary materials on FigShare (about 20,000 pages at https://doi.org/10.6084/m9.figshare.9036884), together with additional analyses not included here. As background information, in all countries, whichever model was used, there was a female first-author citation advantage in more fields than the reverse (Table 2), as previously found with the same data (Thelwall, 2020a).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Full results and details of regression fitting are in the supplementary materials on FigShare (about 20,000 pages at https://doi.org/10.6084/m9.figshare.9036884), together with additional analyses not included here. As background information, in all countries, whichever model was used, there was a female first-author citation advantage in more fields than the reverse (Table 2), as previously found with the same data (Thelwall, 2020a).…”
Section: Resultssupporting
confidence: 76%
“…Although this study found fewer citations per paper for female-authored research overall, subsequent studies with a normalizing technique that did not allow individual highly cited articles to dominate found the opposite overall (Thelwall, 2018). For English-speaking nations, a female citation advantage has been found for most broad fields (Thelwall, 2020a), and for most narrow fields (Thelwall, 2020c). There have also been studies of gender differences in citation rates within individual fields (e.g., Østby, Strand, et al, 2013).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Si bien estos errores no son en general comunes, su frecuencia depende acusadamente del género del autor citado: las investigadoras son citadas como si fueran hombres más de diez veces más a menudo de lo que sucede al contrario, lo que probablemente revela que las citas están influenciadas por el estereotipo de género en la ciencia. El género del autor citante y la disciplina parecen tener poco efecto (contrariamente a lo señalado por Thelwall, 2020).…”
Section: Principales Estudios Sobre Brecha De Género En El Entorno Académicounclassified
“…Como síntesis de nuestra revisión bibliográfica se puede decir que en general las mujeres salen perjudicadas en la mayoría de los casos estudiados, pero en algunas disciplinas en las que son más prolíficas, la situación del reconocimiento a su trabajo está equilibrada (Thelwall, 2020; Torres-Salinas; Muñoz-Muñoz; Jiménez-Contreras) o incluso está a su favor (Nielsen, 2017).…”
Section: Principales Estudios Sobre Brecha De Género En El Entorno Académicounclassified